2006
DOI: 10.1007/s10495-006-0190-x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of both caspase-dependent and -independent pathways in apoptotic induction by hexaminolevulinate-mediated photodynamic therapy in human lymphoma cells

Abstract: Photodynamic therapy (PDT) is a cancer treatment based on the interaction of a photosensitizer, light and oxygen. PDT with the endogenous photosensitizer, protoporphyrin IX (PpIX) induced by 5-aminolevulinic acid (ALA) or its derivatives is a modification of this treatment modality with successful application in dermatology. However, the mechanism of cell destruction by ALA-PDT has not been elucidated. In this study a human T-cell lymphoma Jurkat cell line was treated with PDT using hexaminolevulinate (HAL, he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 32 publications
4
34
0
2
Order By: Relevance
“…This observation is especially noteworthy given that there is some evidence that cells that would normally die via activation of caspases may resort to caspase-independent cell death pathways if caspase activity is persistently inhibited (Furre et al, 2006). Caspase inhibitors did not protect HVC soma area from regression in the current study, although the results from two animals seem to indicate some protection of ipsilateral HVC soma area (Fig.…”
Section: Discussionmentioning
confidence: 48%
“…This observation is especially noteworthy given that there is some evidence that cells that would normally die via activation of caspases may resort to caspase-independent cell death pathways if caspase activity is persistently inhibited (Furre et al, 2006). Caspase inhibitors did not protect HVC soma area from regression in the current study, although the results from two animals seem to indicate some protection of ipsilateral HVC soma area (Fig.…”
Section: Discussionmentioning
confidence: 48%
“…A large number of reports have demonstrated that PDT can kill tumour cells via apoptosis [1,3]. Our previous studies have shown that HAL-mediated PDT induces efficiently apoptotic cell death in several human blood malignant cell lines [15][16][17][18]. The mechanisms of such apoptotic induction by PDT are largely dependent upon the intracellularly initial target sites and biological systems.…”
Section: Discussionmentioning
confidence: 99%
“…In mammalian cells, apoptosis pathway can be divided into caspase-dependent and -independent pathways (24,25). Caspases involved in apoptosis can be grouped into 'apoptotic initiator', such as caspase-9, and 'apoptotic effector', such as caspase-3 based on the substrate specificities and target proteins of caspases (22).…”
Section: Discussionmentioning
confidence: 99%